PENINGKATAN LITERASI SAINS SISWA SD MELALUI IMPLEMENTASI DEEP LEARNING BERBANTUAN INTERACTIVE DIGITAL STORYBOOK BERBASIS AR - Febrianti, Triana; Rosidah, Cholifah Tur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to describe the improvement in science literacy skills of fifth-grade elementary school students through the application of Interactive Digital Storybooks based on Augmented Reality (AR) through deep learning. This research is based on the background of low literacy skills among students, which are influenced by conventional learning methods that lack context and are not yet optimal. The research method used is descriptive quantitative through a one group pretest-posttest design, namely one group of students is given a pretest, then given treatment in the form of the application of interactive digital storybook media based on AR through a deep learning approach, and then given a posttest. The subjects of this study were fifth grade students of SD. Data collection techniques were carried out through science literacy skill tests and questionnaires on student responses to the application of learning media. Data analysis was carried out based on quantitative descriptive by comparing the results of the pretest with the posttest and calculating the percentage increase in science literacy skills. The results of the study proved that there was an increase in students' science literacy skills after the application of the learning media, as evidenced by the posttest scores being higher than the pretest scores. In addition, the students' responses to the use of the media were in the very good category. Thus, it can be concluded that the application of the media.